Model pembelajaran kreatif untuk meningkatkan keterlibatan siswa madrasah ibtidaiyah - Umam, Nuzulul (Maliki Interdisciplinary Journal, 2026)
This This study aims to analyze the effectiveness of a creative learning model in enhancing student engagement in Madrasah Ibtidaiyah (MI) as a solution to low motivation, participation, and activeness in the learning process. The study focuses on how the creative learning model is implemented and the extent to which this approach contributes to changes in students’ learning behaviors in the classroom. The research employs a qualitative approach using a literature review method, with data collected from scientific journals, reference books, research reports, and relevant up-to-date digital sources. Data analysis is conducted using content analysis techniques, including categorizing findings, identifying patterns, interpreting theories, and drawing comprehensive conclusions. The findings indicate that the creative learning model positively influences the enhancement of student engagement across cognitive, affective, and psychomotor domains. Project-based learning, educational games, art activities, group collaboration, and exploratory tasks are shown to increase students’ interest in learning, strengthen intrinsic motivation, and create a more active, enjoyable, and meaningful learning environment. The study also highlights that teacher creativity, varied learning media, and a supportive learning environment play a crucial role in the successful implementation of the creative learning model. Overall, this research provides both theoretical and practical contributions to the field of education, particularly at the Madrasah Ibtidaiyah (MI) level, demonstrating that creative learning is an effective approach to improving the quality of student engagement in the learning process.